The silent information regulator 1 (Sirt1) is a positive regulator of the Notch pathway in Drosophila - Horváth, Matej; Mihajlović, Zorana; Slaninová, Věra; Perez Gomez, Raquel; Moshkin, Yuri; Krejčí (Bruce), Alena (Portland Press Ltd., 2016)
The silent information regulator 1 (Sirt1) has been shown to have negative effects on the Notch pathway in several contexts. We bring evidence that Sirt1 has a positive effect on Notch activation in Drosophila, in the context of sensory organ precursor specification and during wing development. The phenotype of Sirt1 mutant resembles weak Notch lossof- function phenotypes, and genetic interactions of Sirt1 with the components of the Notch pathway also suggest a positive role for Sirt1 in Notch signalling. Sirt1 is necessary for the efficient activation of enhancer of split [E(spl)] genes by Notch in S2N cells. Additionally, the Notch-dependent response of several E(spl) genes is sensitive to metabolic stress caused by 2-deoxy-D-glucose treatment, in a Sirt1-dependent manner. We found Sirt1 associated with several proteins involved in Notch repression as well as activation, including the cofactor exchange factor Ebi (TBL1), the RLAF/LAF histone chaperone complex and the Tip60 acetylation complex. Moreover, Sirt1 participates in the deacetylation of the CSL transcription factor Suppressor of Hairless. The role of Sirt1 in Notch signalling is, therefore, more complex than previously recognized, and its diverse effects may be explained by a plethora of Sirt1 substrates involved in the regulation of Notch signalling.
Keywords: The; silent; information; Sirt1; positive; regulator; the; Notch; pathway; Drosophila